The 'Kickstart to Recovery' programme; a quantitative evaluation of a football programme for mental health service users in an Irish context - CASEY, HANNAH (Trinity College Dublin. School of Medicine. Discipline of Occupational Therapy, 2020)
Football is increasingly being used to support recovery and physical activity for mental health service users. The 'Kickstart to Recovery' programme is a collaboration between occupational therapy and the Football Association of Ireland (FAI), providing a community-based football programme for mental health service users in an Irish context. The aim of this study is to investigate if participants of the 'Kickstart to Recovery' programme experience change in their quality of life, recovery-orientation, engagement in football and social gains after participation in the football programme. This study adopted a quantitative pre-test/ post-test study design with participants from seven 'Kickstart to Recovery' facilitating sites across the Republic of Ireland. Participants completed a questionnaire before and after the football block (5-8 weeks later). The questionnaire comprised of the Short Form 36 (SF-36) measuring the domains of quality of life, the Recovery Assessment Scale – Domain and Stages (RAS-DS), which measures participant's recovery-orientation and the Engagement in Meaningful Activities Survey (EMAS) adapted to measure the meaning one attributes to football. Social gains were also measured by isolating the domains of 'Social Functioning' of the SF-36 and 'Connecting and Belonging' of the RAS-DS. A total of 40 pre-test questionnaires were completed, of which 27 also completed the post-test questionnaire. Two statistically significant results were found when comparing pre- and post-programme results; the SF-36 'Energy/Fatigue' domain for the total sample and the RAS-DS 'Mastering My Illness' domain for those who participated in the programme for the first time. In addition, statistically significant results were found for domains of 'Social Functioning' and 'Emotional Wellbeing' when conducting an inter-group comparison of the duration of the programme blocks. It later emerged these sites incorporated a social aspect into their sessions. With the absence of a control acknowledged, the 'Kickstart to Recovery' programme is attributed as a factor contributing to these results. These significant findings, however, demonstrate the potential benefits of energy improvements throughout participation, development of symptom management and the importance of a structural social aspects in the sessions. Results that did not show significance also provide information on possible areas not currently being addressed by the programme, such as fostering hope, aspects of quality of life and social gains. Further to these results, this study explored the structure of the programme and provides recommendations based on current literature for promoting community integration, recovery, and a gender focus in the 'Kickstart to Recovery' programme.
APPROVED
Keywords: Occupational Therapy; Football; Mental Health; Recovery